On the crack initiation and heterogeneous deformation of Ti-6Al-4V during high cycle fatigue at high R ratios. (August 2019) - Bandyopadhyay, Ritwik; Mello, Alberto W.; Kapoor, Kartik; Reinhold, Michael P.; Broderick, Thomas F.; Sangid, Michael D.
Highlights: Anomalous mean stress effects are observed in Ti-6Al-4V at high R ratios. A critical soft-hard-soft grain combination is associated with crack initiation. The percentage of grains being plasticized is lower at higher R ratios. Multiple families of slip systems are activated at higher R ratios. Pyramidal slip is significant in a macrozone with c-axes parallel to the loading axis. Abstract: In engineering practice, mean stress corrections are employed to assess the fatigue performance of a material or structure; albeit this is problematic for Ti-6Al-4V, which experiences anomalous behavior at high R ratios. To address this problem, high cycle fatigue analyses were performed on two Ti-6Al-4V specimens with equiaxed alpha microstructures at a high R ratio. In one specimen, two micro-textured regions (MTRs) having their c-axes near parallel and perpendicular to the loading direction were identified. High-resolution digital image correlation (HR-DIC) was performed in the MTRs to study grain-level strain localization. In the other specimen, DIC was performed on a larger area and crack initiation was observed in a random-textured region. To accompany the experiments, crystal plasticity finite element simulations were performed to investigate the mechanistic aspects of crack initiation, and the relative activity of different families of slip systems as a function of R ratio. A critical soft-hard-soft grain combination was associated with crack initiation indicating possible dwell effect at high R ratios, which could be attributed to the high-applied mean stress and high creep sensitivity of Ti-6Al-4V at room temperature. Further, simulations indicated more heterogeneous deformation, specifically the activation of multiple families of slip systems with fewer grains being plasticized, at higher R ratios. Such behavior is exacerbated within MTRs, especially the MTR composed of grains with their c-axes near parallel to the loading direction. These features of micro-plasticity make the high R ratio regime more vulnerable to fatigue damage accumulation and justify the anomalous mean stress behavior experienced by Ti-6Al-4V at high R ratios.